2017
DOI: 10.3390/genes8120348
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNAs in Pediatric Airway Diseases

Abstract: Non-coding RNAs (ncRNAs) are involved in the regulation of numerous biological processes and pathways and therefore have been extensively studied in human diseases. Previous reports have shown that non-coding RNAs play a crucial role in the pathogenesis and aberrant regulation of respiratory diseases. The altered expression of microRNAs (miRNAs) and long non-coding RNAs in blood and also locally in sputum or exhaled breath condensate influences lung function, immune response, and disease phenotype and may be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 99 publications
0
26
0
Order By: Relevance
“…150 lncRNAs can act as competing endogenous RNAs (ceRNAs) to bind to complementary microRNAs and prevent them from binding to their target mRNAs. 151153 In asthma, lncRNAs (i.e., ceRNAs) indirectly affect the levels of Foxp3 and RORγt by targeting their specific miRNAs and therefore contribute to the T reg /Th17 imbalance, which is a hallmark of asthma pathogenesis. 154 Although lncRNAs can regulate the T reg /Th17 balance, other potential mechanisms still need to be investigated.…”
Section: Foxp3-rorγt Signaling Pathwaymentioning
confidence: 99%
“…150 lncRNAs can act as competing endogenous RNAs (ceRNAs) to bind to complementary microRNAs and prevent them from binding to their target mRNAs. 151153 In asthma, lncRNAs (i.e., ceRNAs) indirectly affect the levels of Foxp3 and RORγt by targeting their specific miRNAs and therefore contribute to the T reg /Th17 imbalance, which is a hallmark of asthma pathogenesis. 154 Although lncRNAs can regulate the T reg /Th17 balance, other potential mechanisms still need to be investigated.…”
Section: Foxp3-rorγt Signaling Pathwaymentioning
confidence: 99%
“…Expression profiling of non-coding RNAs (ncRNAs) is emerging as an approach for identifying new therapeutic targets for CF, based on the crucial role these molecules play as master regulators of gene expression and biological processes [53]. Although there are several species of ncRNAs, microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) are the two most studied regulatory ncRNAs because they have been implicated in many human diseases [54].…”
Section: Emerging Targets For Transcriptome Profilingmentioning
confidence: 99%
“…LncRNAs are large (>200 nucleotides in length) ncRNA species that localize to the nucleus or cytoplasm, with a capacity to interact with DNA, RNA, and protein [61]. The regulatory role of lncRNAs in biological processes such as chromatin modification, transcription, and post-transcriptional processing, and intracellular trafficking is well-documented [53,62]. Aberrant expression of lncRNAs has been implicated in many respiratory diseases [63] including CF, where BGas lncRNA was demonstrated to regulate CFTR expression [64].…”
Section: Emerging Targets For Transcriptome Profilingmentioning
confidence: 99%
“…According to recent publications, no direct reports indicate that piRNAs may play effective role in the regulation of HR4 during the pathogenesis of AR, further explaining the specific pattern of piRNAs in the positive control groups. However, there are various publications, in deed confirmed that piRNAs may contribute to the pathogenesis of AR via some specific regulatory mechanisms like interacting with PTEN (Phosphatase and Tensin homolog) ( Alexandrova et al, 2016) and PI3k (Phosphoinositide 3-kinase) (Alexandrova et al, 2016;Narożna et al, 2017). Considering that traditional HR4 antagonists only block HR4 by physical binding, however, our newly identified peptides block HR4 biological functions by triggering specific immune response against HR4.…”
Section: Discussion On the Differential Small Rna Distribution Patternsmentioning
confidence: 85%